Kesiapan Prasarana Mitigasi Bencana Pada Kawasan Rawan Bencana Erupsi Gunung Berapi Kabupaten Magelang - Ivan Yusuf; Widjonarko Widjonarko (Teknik PWK (Perencanaan Wilayah Kota), 2018)
Magelang regency has high volcanic eruption risk level from high to low. The 2010 eruption disaster was the most explosive among the others in the past decade. The high level of hazard with unpreparedness from community and the government in dealing with disasters in 2010 made poor evacuation. Based on these problems the assessment preparedness level of disaster infrastructure is important. Because it can reduce the impact of damage and disadvantages obtained by the community. The research question is "Is disaster mitigation infrastructure in volcano disaster prone region of Mount Merapi Magelang ready for emergency and post-disaster conditions?" The purpose of this study is to assess the preparedness of mitigation infrastructure such as evacuation route, evacuation building, early warning system, sanitation and water in disaster-prone areas of volcanic eruption in Magelang Regency, especially Dukun District. The data are collected from field observation and interview. This research used quantitative method, and the scoring analysis assessment used few parameters based on the readiness of each infrastructure.The analysis shows that the disaster mitigation infrastructure of Magelang Regency, especially Dukun district is not ready for all residents in KRB III area. The result of analysis shows that 57% of disaster infrastructures have feasible condition and function. The result caused the level of disaster infrastructure in Dukun Sub-district to be "Almost Ready". Infrastructures that need to be improved are toilet facilities, water facilities, and evacuation site. Infrastructures that have been categorized as ready are early warning systems, garbage and evacuation routes. Some of the existing infrastructure is ready for use but still need improvement or additional infrastructure to serve all disaster prone area community.